KEMAUAN WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN MEMBAYAR PAJAK DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Eny Kustiyah, Yuli Chomsatu Samrotun (MAJALAH ILMIAH GEMA, 2015)
This research aims to analyze the factors that affect individual taxpayers in meeting their to pay taxes obligation. Independent variables in this research are the awareness of tax paying, knowledge and understanding of taxation laws, a good perception of the effectiveness of the tax system and the service of iscus, while the dependent variable is the willingness to pay taxes. This research uses random sampling methods in data collection. Data source is primary data, by giving questionnaires to respondents. Respondents in this research is individual taxpayer who listed in Surakarta Primary Tax Ofice. Data analysis using multiple linear regression analysis and SPSS 17 program. Partially, the results of the analysis and hypotesis shows that awareness of tax paying and a good perception of the effectiveness of the tax system have signiicant impact on willingness to pay taxes, while knowledge and understanding of taxation laws and the service of iscus didnât have signiicant impact on willingness to pay taxes. Simultaneously, all of the independent variables in this research have signiicant impact on willingness to pay taxes. Keywords: Willingness, awareness, knowledge, understanding, perception, iscus